2020
DOI: 10.1111/vsu.13379
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term arthroscopic assessment of intra‐articular allografts for treatment of spontaneous cranial cruciate ligament rupture in the dog

Abstract: Objective: To assess the 12-month survival of intra-articular, decellularized allografts for the treatment of cranial cruciate ligament disease (CCLD) in dogs. Study design: Prospective case series.Animals: Twenty client-owned dogs with spontaneous CCL rupture. Methods: Affected stifles were treated solely by implantation of an intra-articular, decellularized, deep digital flexor tendon allograft. Functional outcome was evaluated at baseline and at 6 and 12 months after surgery with the Liverpool Osteoarthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 36 publications
(39 reference statements)
1
27
1
Order By: Relevance
“…It also increases the chance that a measurable change (improvement after an intervention) can be documented in the study. The asymmetry index is a valuable outcome measure in longitudinal studies, 23,24 but it is ideal if these data are reported in conjunction with other GRFs.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…It also increases the chance that a measurable change (improvement after an intervention) can be documented in the study. The asymmetry index is a valuable outcome measure in longitudinal studies, 23,24 but it is ideal if these data are reported in conjunction with other GRFs.…”
Section: Subjectsmentioning
confidence: 99%
“…15,34,35 Fixed velocity ranges have also been used in many clinical trials of homogenous and heterogeneous populations of lame dogs. 14,24,[36][37][38][39] However, when using a fixed velocity in a heterogenous population, some dogs may be required to walk or trot outside of their preferred velocity. Although experiences vary, a larger number of passes over the force platform may be needed to obtain the required number of valid trials.…”
Section: Fixed or Preferred Velocity Rangementioning
confidence: 99%
See 2 more Smart Citations
“…Since PVF and VI are not independent variables, a multivariate approach that evaluated PVF and VI together was used to evaluate limb function. [19][20][21] A symmetry index was calculated for pre-and postoperative PVF and VI using the formula SI…”
Section: Gait Analysismentioning
confidence: 99%